The Effect of Acceptance and Commitment Therapy on Self-Efficacy Santri - Faizah, Imamatul; Hasina, Siti Nur; Sari, Ratna Yunita; Rohmawati, Riska; Putri, Rahmadaniar Aditya (Indonesian Journal of Global Health Research, 2024)
Low Self-Efficacy is a problem for every new santri who lives in Islamic boarding schools. Acceptance and commitment therapy (ACT) is an empirical therapy that aims to increase psychological flexibility as a basis for handling self-acceptance, self-awareness and self-efficacy in psychotherapy. Objective: The aim of this study was to analyze the effect of acceptance and commitment therapy on self-efficacy of new santri. Methods: This study was designed as a quasi-experimental with a pre-test and post-test control group or a non-equivalent control group. The sampling technique in this study was purposive sampling with 22 treatment group respondents and 22 control group respondents. The variables are acceptance and commitment therapy as independent variables and self-efficacy as dependent variable. This study used the General Self-Efficacy Scale (GSES) instrument which has been adapted to Indonesian. The statistical test used t-test with α ≤ 0.05. Results: The treatment group showed a difference in the average value of self-efficacy between before and after participating in acceptance and commitment therapy as the results of paired sample t test obtained a value of p = 0.000 in treatment group and p = 0.197 in control group. Conclusion: Acceptance and commitment therapy has an effect on self-efficacy of new santri at Islamic Boarding School of Daruttaqwa Gresik. ACT can be used as an alternative of nursing interventions especially in islamic boarding schools.